Are we Training Enough of Communication Skills and Patient Psychology Required in Dental Practice - Varsha Murthy (Journal of Clinical and Diagnostic Research, 2017)
The aim of this review is to discuss about lacunae in the areas of Communication skills and Patient psychology teaching in the dental set up in India. A literature search was performed using various databases and other resources. Data obtained was reviewed to obtain the work done in this field. It was found that there is currently no clear data in literature as to how much and how well students are taught about communication and behavioural skills and patient personality in dental curriculum in India. Pinpointing such lacunae can help dental colleges and universities to focus on the emphasis of their approaches to teaching about communication skills and psychology of the patient. Identification of future research area in this field is the need of the time for future discovery and progress in this overlooked field.